Optimization of cinnamaldehyde extraction and antioxidant activity of Ceylon cinnamon extract - Zetty Shafiqa Othman; Mohamad Yusof Maskat; Nur Hasyareeda Hassan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cinnamon is a spice obtained from the inner bark of cinnamomum tree. Cinnamaldehyde, the major consitituent of the cinnamon essential oil is responsible for the flavor and aroma of whole cinnamon. Cinnamaldehyde have various medicinal application including neuroprotection. Thus, this study intends to identify the optimal condition for cinnamaldehyde extraction with high antioxidant activity of cinnamon extract. Responses (cinnamaldehyde yield, TPC, and TEAC) were optimized using response surface methodology (RSM) by employing two factors (temperature and extraction time) based on a three level face centered central composite design (CCD). Level of extraction temperature used were 30 °C, 55 °C and 80 °C, while extraction time were 4, 7, and 10 h. The CCD consisted of 8 experimental point and 5 replicates of central points. The optimal conditions to obtain maximum cinnamaldehyde yield, TPC and TEAC were extraction temperature of 37 °C at 5 h extraction time with predicted cinnamaldehyde yield of 3.05 mg/g, TPC of 682.17 mg GAE/ g and TEAC of 821.57 µmol TE/g respectively. The experimental values obtained for the cinnamaldehyde yield, TPC, and TEAC under the optimal condition were 3.11 ± 0.71 mg/g, 682.66 ± 54.85 mg GAE/g, and 817.89 ± 9.03 µmol TE/g. The proximity between experimental and prediction values verify the fitness of RSM models applied for determination of optimal condition for cinnamaldehyde extraction.